Effective capacity of dual-hop networks with a concurrent buffer-aided relaying protocol - Phan, Khoa T.; Tho Le-Ngoc (2014 IEEE International Conference on Communications (ICC), 2014)
This paper presents an analysis of the achievable effective capacity of a dual-hop network with buffer-aided source and relays using a concurrent relay selection protocol. The source and relays are subject to constraints on the maximum allowable delay violation probabilities. The effective capacity under such statistical delay constraints is derived as a function of the source and relay signal-to-noise power ratios (SNRs), delay exponents, number of relays, and fading distributions. Illustrative results show the effective capacity under various SNR regions and statistical delay constraints. It is seen that more stringent delay constraints significantly reduce the effective capacity of dual-hop networks.